Tradisi Manakib-an Sayyidah Khadijah al-Kubra di Mushalla Daruttaqwa Samarinda dan Pengaruhnya Terhadap Masyarakat - Muhammad Fajar Adyatama (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This paper aims to examine the manaqib tradition of Umm al-Mu'minin, Sayyidah Khadijah al-Kubra in Langgar Daruttaqwa, Sempaja, Samarinda. The tradition of reading manaqib also exists historically with the culture and psychology of the community from time to time which then inevitably influences changes in people's behavior in some or all aspects of the life of the perpetrators. The Manaqib tradition in Langgar Daruttaqwa is held every night, ba'da maghrib, on the 11th of the Qomariyah month (hijri year), this election is in accordance with the date of the death of Sayyidah Khadijah al-Kubra, namely on the 11th of Ramadan in the 10th year of the prophethood, three years before the Prophet's migration. to Yathrib (Medina). Sayyidah Khadijah died at the age of 65 when the Prophet was about 50 years old. This Manakib was carried out with sources that were in accordance with the guidance of Tuan Guru. The wisdom for the culture of our ancestors as long as it does not conflict with the texts of the Qur'an and Hadith, expects an abundance of blessings from Sayyidah Khadijah al-Kubra, so that they include people who love the auliya Allah, especially the experts of the Prophet's temple. This activity also has elements and values ​​of moral education, such as making this activity a forum for community gathering, and motivating children in particular to take part in the prosperity of violators and Islamic symbols.